Synthesis, spectral characterization, antimicrobial, DNA binding and antioxidant studies of Co(II), Ni(II), Cu(II) and Zn(II) metal complexes of novel thiosalen analog N2S2 - Seda, Sabry Hamed; Abdel Aziz, Ayman Ahmed (European Journal of Chemistry, 2015)
Co(II), Ni(II), Cu(II) and Zn(II) metal complexes of a quadridentate Schiff base with a N2S2 donor set derived from condensation of benzene-1,2-dicarboxaldehyde(o-phthaldehyde) with 2-aminothiophenol were synthesized and characterized by elemental microanalyses, molar conductance, magnetic susceptibility measurements and spectroscopic techniques viz, FT-IR, 1H NMR, EPR and UV-Vis. The spectral data showed that, the ligand acts as a tetradentate ligand and the bonding sites were deprotonated thiol-S groups and azomethine nitrogen atoms. The results have indicated that the complexes exhibited tetrahedral geometry arrangements except Cu(II) complex that exhibited square planar geometry. Preliminary antimicrobial screening shows the promising results against both bacterial and fungal strains. The interaction of the Schiff base ligand and its complexes with calf-thymus DNA (CT-DNA) has been monitored by UV-Vis, competitive fluorescence titration and hydrodynamic techniques (Viscosity measurements). The results have indicated that the ligand and its complexes bind to CT-DNA through intercalation mode. Moreover, investigations of antioxidative properties showed that all the compounds have strong radical scavenging properties. The data have shown that, among all compounds, Cu(II) complex has exhibited better biological activity than other complexes and the parent ligand.